The Use of Bacteria in Cancer Treatment: A Review from the Perspective of Cellular Microbiology. (8th August 2022) - Mills, Hilla; Acquah, Ronald; Tang, Nova; Cheung, Luke; Klenk, Susanne; Glassen, Ronald; Pirson, Magali; Albert, Alain; Hoang, Duong Trinh; Van, Thang Nguyen
Abstract : Cellular microbiology, which is the interaction between harmful microbes and infected cells, is important in the determination of the bacterial infection processes and in the progression of data of different cellular mechanisms. The therapeutic role of bacteria has gained attention since the known methods such as radiation, chemotherapy, and immunotherapy have got drawbacks. Bacteria have demonstrated a favorable impact in treating cancer through eradication of tumors. Bacteria, in cancer treatment, have proven to be promising and have been shown in some of the previous work that it can successfully suppress the growth of tumors. In this paper, we analyzed the difficulties and settlement for using bacteria in cancer therapy as well the mechanisms in which bacteria works in order to achieve tumor eradication. Future works may focus on the use of bacteria along with other treatments in order to achieve effective tumor therapy.